Construção Sócio-Histórica das Configurações Familiares: Uma análise a partir da atuação dos profissionais da Assistência Social no Estado da Paraíba - Leão, Ricardo de Holanda (2016)
The Brazilian family passed through inner transformations for centuries, since the Portuguese colonization. Such European influences had become effective as time passed by, culminating with the advent and with the development of technology, essentially with the discovery of the DNA, for instance, among other factors. By the beginning of the twentieth century, the movements and social protests in support of the women became stronger leading to a new perspective for the modification of the Brazilian family, and consequently of the Brazilian states. The state of Paraíba, which has been immersed in the context of this historical development, also passes along the time through the social, political, cultural, and economical transformations, acquired its own singularities, as well as those from the territories that surrounds it. So, the present research has as its general objective to identify the historical elements which constitute the different families configurations inside the paraibana society. Moreover, as specific objectives, were presented the reflection about the progress of the capitalist system as a historic determinant of modification into the families‟ configurations. Besides, it was analyzed how the public politics, which compose the social security, can guarantee the rights of these different families configurations, and finally, the identification of the understanding of the PNAS professionals who work directly with the paraibanas families, and how they can guarantee the right of such families independently of their configurations. The research configures itself as a critical-analytical study, with a quantitative-qualitative feature as a methodological procedure of analyses for the object. The use of a theoretical-methodological referential centered in the understanding of the family, of the state, of the social politics, and of the capitalism, besides the conceptual variants contained in the term family, were constructed from the conceptions of authors, such as Behring (2008), Carvalho (2008), Dias (2008), Engels (s/d), Esping-Andersen, (1990), Freyre (2013), Lessa (2012), Mioto (2004, 2015), among others, which showed to be indispensable in this research. Beyond this first approach, the research is a result of the investigations concerning the conceptions and the acting of the professionals who work in the Nacional Politics of Social Assistance – PNAS (in Portuguese). Such professionals provided relevant data for our debate, which were collected via a field research, intermediated by the event CapacitaSuas, occurred in the city of João Pessoa – PB (in one of its phases) between September 21 and September 25 of 2015. The field research was divided in three parts in order to reinforce the notes previously listed in different contexts: the first step is based on questionnaires applied to social assistants of the mentioned event; the second occurred from the formation of a focal group also constituent of social assistants; and the third was composed by workshops in classroom with other professional categories working in the PNAS. Then, we had an approximate number of 130 professionals who directly contributed with the research, resulting in several conceptions concerning the family and its referrals to the realization of the social rights applicable in the context of the social assistance.